Refusal of Smoking Among Male Adolescents in Sampang Madura: A Qualitative Study - Sutha, Diah; Ambag, Silvia Catalan; Novianti, Siti; Christine (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: The high prevalence of smoking among adolescents is a serious concern for society and the government. Many studies have been conducted to examine the reasons why adolescents start smoking and how to prevent smoking behavior among adolescents. In the midst of high rates of smoking behavior among adolescents, it is also very interesting to study smoking refusal among adolescents which can later provide information for prevention programs in helping adolescents avoid smoking behavior. Objectives: To describe the phenomenon regarding the rejection of adolescent smoking behavior. Methods: This research is qualitative research that uses in-depth interviews with 17 teenagers as informants. This research was conducted in the District of Sampang Madura from February 2021 to June 2021. The selection of informants then followed the information from the informants who completed the interview (snowball sampling). Results: Based on the results of the study it was found that adolescents who have peers who do not smoke tend to easily reject smoking behavior. Refusal to smoke by adolescents includes health factors, impact on quality of life, societal norms, and appearance. The existence of orders from the family environment to avoid smoking behavior was also mentioned by adolescents as a reason not to smoke. Conclusions: Adolescent rejection of smoking behavior can be used as a reference in smoking behavior prevention programs and also as material for evaluating intervention programs that can help adolescents to quit smoking.